2017
DOI: 10.28945/3641
|View full text |Cite
|
Sign up to set email alerts
|

Towards “Operating Within” the Field: Doctoral Students’ Views of Supervisors’ Discipline Expertise

Abstract: Aim/Purpose: This paper considers the role of supervisors’ discipline expertise in doctoral learning from a student perspective. Background: Doctoral students need to develop expertise in a particular field of study. In this context, developing expertise requires doctoral students to master disciplinary knowledge, conventions and scholarship under the guidance of supervisors. Methodology : The study draws on a mixed-method approach, using an online survey and semi-structured interviews conducted with doctora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
2
16
0
3
Order By: Relevance
“…First of all, this reveals how important it is that before a new PhD student starts, it is ensured that he or she will get along with the supervisor and vice versa. This is in line with the ever increasing literature about the importance of a good fit (or match) between the student and supervisor, both academically and personally (Gube et al 2017;Woolderink et al 2015). Also, throughout the PhD trajectory, both supervisor and PhD student should keep investing in the relationship, and regularly explicitly discuss mutual expectations and evaluate whether the supervisor's support meets the PhD student's needs.…”
Section: Implications For Practicesupporting
confidence: 79%
See 1 more Smart Citation
“…First of all, this reveals how important it is that before a new PhD student starts, it is ensured that he or she will get along with the supervisor and vice versa. This is in line with the ever increasing literature about the importance of a good fit (or match) between the student and supervisor, both academically and personally (Gube et al 2017;Woolderink et al 2015). Also, throughout the PhD trajectory, both supervisor and PhD student should keep investing in the relationship, and regularly explicitly discuss mutual expectations and evaluate whether the supervisor's support meets the PhD student's needs.…”
Section: Implications For Practicesupporting
confidence: 79%
“…Working on a project that is not closely related to the supervisor's research was also related to dissatisfaction and considering quitting. This shows thatin addition to the importance of a good relationshipa good academic match between PhD candidate and supervisor is important, as Ives and Rowley (2005) and Gube et al (2017) also emphasise.…”
Section: Project Characteristicsmentioning
confidence: 84%
“…Postgraduate students in Gube et al's (2017) study argued that discipline-expert supervisors were appreciated because they were strongly connected with the discipline context and therefore "provide[ed] support in relation to research direction and content-specific feedback" (p. 10). This is a sharp contrast to experiences reported here, where some students did not receive positive or clear feedback from the supervisor because the supervisor lacked relevant knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, supervisor lack of research expertise or knowledge (Khozaei et al, 2015) in a specific discipline has led students experiencing research failure: for example, postgraduate students in Khozaei et al's (2015) study pointed out that, by not having a supervisor who had in-depth knowledge on statistical analyses, understanding of the whole research proposal was jeopardised. Gube et al (2017) found that postgraduate students do value discipline-expert supervisors because the latter speed up research progress by "connecting [students] with appropriate literature and contacts in the field" (p. 7). As a result, "the role of supervisors has been often cited as an important contributing factor to the success of graduate students" (Khozaei et al, 2015, p. 449) and supervisors neglecting their responsibilities as supervisors can be a major interruption to their students' research progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although doctoral students should transform from course-takers into autonomous researchers, supervisors can facilitate the development of independent scholars by offering their expertise and guidance. When supervisors have knowledge in the discipline of the student, it can hasten their progress, as supervisors can assist the students overcoming intellectual barriers (Gube, Getenet, Satariyan, & Muhammad, 2017). Evidence shows that student progress is associated with faculty connections (Anderson, Cutright, & Anderson, 2013); therefore, identifying technology that enables communication is warranted.…”
Section: Online Doctoral Studentsmentioning
confidence: 99%